IMMOBILIZATION OF HUMIC ACID ON CHITOSAN BEADS BY PROTECTED CROSS-LINKING METHOD AND ITS APPLICATION AS SORBENT FOR Pb(II) - Radna Nurmasari; Uripto Trisno Santoso; Dewi Umaningrum; Taufiqur Rohman (Universitas Gadjah Mada, 2010)
Immobilization of humic acid (HA) on chitosan beads has been done using a protected cross-linking reaction method and the product was then utilized as sorbent for Pb(II). Protection of the active sites of HA was carried out by interacting HA with Pb(II) before performing the cross-linking reaction in order to maintain its adsorption capacity. Protected-HA was cross-linked with chitosan beads using glutaraldehyde in order to obtain sorbent insoluble both in aqueous acidic and basic solution. The result showed that the amount of immobilized HA on beads chitosan was 88.60% by weight. The adsorption capacity of the protected-sorbent beads for Pb(II) was 784 mg/g. As a comparison, the adsorption capacity of the non-protected sorbent beads for Pb(II) was only 142 mg/g.